Expression identification of three OsWRKY genes in response to abiotic stress and hormone treatments in rice - Jiangdi Li; Yating Chen; Rui Zhang; Bin Wu; Guiqing Xiao (Plant Signaling & Behavior, 2023)
WRKY transcription factors are critical for plant growth, development, and adaptation to stress. This paper focuses on the expression characteristic to abiotic stress and phytohormones of OsWRKY24, OsWRKY53, and OsWRKY70. Three OsWRKY TFs contained two conserved domains and there were multiple cis-elements in response to adversity stress and hormone signaling in their promoters. Real-time PCR analysis revealed their widespread expression in normal tissues during seedling and heading stages. Under various stresses such as darkness, low temperature, salt, and drought, or treatment with hormones like ABA, SA, MeJA, and GA, transcript levels of these genes had changed significantly in wild-type seedlings. The expression level of OsWRKY24 was upregulated by darkness, cold, SA, and MeJA but downregulated by salt, drought, ABA, and GA treatments. The transcripts of OsWRKY53 were induced by darkness, low-temperature, salt, drought, ABA, and JA, while inhibited by SA and GA. In addition, OsWRKY70 expression level was elevated under darkness, low-temperature, SA, and JA but suppressed with salt, drought, ABA, and GA. These findings provide valuable insights into the regulatory mechanisms by which WRKY TFs adapt to stress via plant-hormone signaling.